(untitled) (SCIENCE TIME JOURNAL, 2026)
In order to accomplish narrative reclamation, this essay examines the role of metafictional elements in Barbara Chase-Riboud’s 1979 historical novel Sally Hemings. This study investigates the contestability of speculative fiction used to ‘voice’ an enslaved woman whose own perspective was routinely left out of the patriarchal archive. It is based on the theoretical frameworks of Patricia Waugh and Linda Hutcheon. The analysis looks into the moral dangers of portraying a relationship characterized by institutional slavery as a ‘poignant love story’ and examines the reasoning behind Nathan Langdon, the proxy character, as a metafictional device that mediates the white gaze. The findings imply that although Chase-Riboud successfully gives Hemings a human face, her narrative strategies force a critical confrontation with the institutional barriers that continue to filter and mediate the lives of the enslaved in the modern imaginary.